Bone metastasis in differentiated thyroid cancer: Spanish multicenter study of clinical characteristics, survival and prognostic factors - Dueñas-Disotuar, Suset; Piñar-Gutiérrez, Ana; de Lara-Rodríguez, Irene; Sastre-Marcos, Julia; Anda-Apiñániz, Emma; Oleaga-Alday, Amelia; Galofré, JC; Orois, Aida; Alcázar-Lázaro, Victoria; Martínez-Guasch, Laia; Sánchez-Ragnarsson, Cecilia; Gálvez-Moreno, María Ángeles; et al. (Frontiers in Endocrinology, 2024)
Objective: This study describes the characteristics, survival and prognostic factors in a cohort of patients with bone metastases (BM) from differentiated thyroid carcinoma (DTC). Methods: This was a multicenter retrospective observational study conducted in Spain, including patients diagnosed with DTC and BM between 1980 and 2022. A Cox regression analysis was performed to examine prognostic factors for survival. Kaplan-Meier and log-rank tests were performed for survival analysis and comparison between groups. Results: A total of 133 patients were included with a median follow-up of 40 (17-70) months. Seventy patients (52.6%) had BM at the initial diagnosis. Fifty-two (39.1%) had follicular carcinoma. Sixty-six (49.6%) presented multiple BM. The most frequent location was the spine (63.2%). Other metastases were present at diagnosis in 88 (66.2%), mainly lung (60.9%). BM were treated with I131 in 91 (68.4%) patients, with BM uptake in 63 (47.4%). Fifty-six (42.1%) received treatment with multikinase inhibitors. Fifty-three (3.9%) had skeletal-related events. Seventy-two (54.1%) died. The 3-, 5- and 10-year survival was 53.5, 39.5% and 28.5%, respectively. Significant prognostic factors in the multivariate analysis were the presence of lymph node metastases (N1) HR 1.71 (95% CI 1.005-2.098; p=0.048), BM treatment with I131 HR 0.532 (95% CI 0.304-0.931; p=0.027) and age ≥67 years at BM diagnosis HR 1.991 (95% CI 1.142-3.47; p=0.015). Conclusions: Survival of DTC patients with BM treated in a Spanish cohort was 39.5% at 5 years and 28.5% at 10 years. Patients with BM treated with I131 appear to have a better outcome in terms of mortality and the presence of lymph node involvement and age over 67 years were associated with higher mortality.